Russian-Turkish Official Contacts in the Azov Sea Region in the Summer of 1699 (to the Prehistory of the Mission of Envoy Extraordinary Yemelyan Ukraintsev) - Pyotr Avakov (Крымское историческое обозрение)
The article examines official contacts between the Russian Tsardom and the Ottoman Empire in the Sea of Azov Region during the preparation of the embassy of Y.I. Ukraintsev to Constantinople in 1699. The parties were represented by officials who did not have diplomatic status: Admiral F.A. Golovin, who arrived in Azov and the Beylerbey of Kefe Tatar Murtaza Pasha, who was in Kerch. The Azov Palatine (Governor) participated in organizing communication between them, within the framework of the so-called border diplomacy. The Armistice of Karlowitz established in 1699 and the mutual hope for concluding a long-term peace served as a favorable background for the development of bilateral relations at the local level. It is shown that, largely thanks to successfully conducted negotiations, including through envoys and correspondence, the admiral and the beylerbey managed to organize a temporary stay in the Kerch Strait for a squadron of the Azov Fleet and the dispatch of a Tsar’s Envoy to Constantinople on a Russian warship. The source base for the study consisted mainly of archival documents, some of which were introduced into scientific circulation for the first time.